Global pandemics and moratorium of investment claims: A perspective from Indonesia - Yetty Komalasari Dewi (Cogent Business & Management, 2023)
The outbreak of the Corona Virus Disease 2019 (COVID-19) has given rise to the intersection of foreign investment protection in connection with adverse regulatory changes and the right of host states to regulate the public interest. Countries have enacted a multitude of policies in pursuit of public health and in handling the repercussions of the pandemic including losses to foreign investors, thus giving rise to arbitral claims. In response, governments may impose customary law defense through the doctrine of police powers under the banner of health reasons. This article features an analysis of Indonesia as a sample country to illustrate possible claims that could arise from its regulatory responses to COVID-19 and possible protections that it can rely upon. In recalibrating the investor-State dispute settlement system, a moratorium on investment claims arising from the pandemic should be endorsed as part of a wider set of reforms.
Keywords: 650; COVID-19; Indonesia; investment arbitration; ISDS; moratorium